2012
DOI: 10.1038/clpt.2012.66
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Drug Outcomes Through Pharmacogenetics: A Case for Preemptive Genotyping

Abstract: Routine integration of genotype data into drug decision-making could improve patient safety, particularly if many relevant genetic variants can be assayed simultaneously before target drug prescribing. The frequency of pharmacogenetic prescribing opportunities and the potential adverse events (AE) mitigated are unknown. We examined the frequency with which 56 medications with known outcomes influenced by variant alleles were prescribed in a cohort of 52,942 medical home patients at Vanderbilt University Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
179
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(190 citation statements)
references
References 32 publications
8
179
2
1
Order By: Relevance
“…Many patients would be willing to undergo testing again in the future, and many indicated that they'd prefer to undergo preemptive testing to avoid any delays in treatment. It has been estimated that the use of preemptive PGx testing could be helpful in preventing a significant number of adverse events given the multiple commonly used medications with known PGx interactions that patients will likely be prescribed [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Many patients would be willing to undergo testing again in the future, and many indicated that they'd prefer to undergo preemptive testing to avoid any delays in treatment. It has been estimated that the use of preemptive PGx testing could be helpful in preventing a significant number of adverse events given the multiple commonly used medications with known PGx interactions that patients will likely be prescribed [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…19 Despite this demonstrated feasibility, only a handful of institutions have successfully implemented and documented clinical implementation of pharmacogenomic testing, using a preemptive genotyping approach where data for multiple pharmacogenes are acquired at the same time and electronically stored for future use. 20 This approach enables decreased individual genotype costs and development of advanced clinical decision support tools for use by frontline pharmacists and other clinicians (similar to, but more advanced than, drug allergy or drug-drug interaction information). In this paradigm, medication order entry automatically triggers a search for relevant drug-gene interactions for the patient; if clinically actionable variants are identified, the system guides the clinician toward appropriate individualized therapy.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…In addition, a point-of-care CYP2C19 genotyping device with a turnaround time of about an hour has been developed and recently used to explore the feasibility of incorporating CYP2C19 * 2 testing into clinical protocol for antiplatelet dosing [102]. In addition to technology advances, the concept and adoption of preemptive (preprescription) genotyping [5,[103][104][105] with result stored in electronic medical record for subsequent use would also help minimize the inconvenience of time delay in test reporting. The issue of health informatics technology will be discussed in a later section.…”
Section: Integration Of Pharmacogenomic Biomarker Within the Healthcamentioning
confidence: 99%